2017
DOI: 10.15516/cje.v19i0.2433
|View full text |Cite
|
Sign up to set email alerts
|

The Teacher 's Role in the Creative Teaching of Literacy / Uloga učitelja u kreativnom poučavanju pismenosti

Abstract: The teacher plays the central role in the educational process. In Croatian language teaching, the teacher represents a role model for his or her students in both speaking and writing. This is why it is very important to encourage teachers in language and language expression classes to stimulate and develop the creative thinking of their students by promoting new and interesting ways of finding different solutions to various problems. The creative teaching of literacy involves the use of different methods and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The results showed that there are strong obstacles related to students, curricula, and teaching environments [47]. Many studies have stimulated creativity and creative teaching in higher education, and teaching staff's practice in methods of developing creative thinking [5,20,25,48].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that there are strong obstacles related to students, curricula, and teaching environments [47]. Many studies have stimulated creativity and creative teaching in higher education, and teaching staff's practice in methods of developing creative thinking [5,20,25,48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective teaching is creative teaching, and thus, it is imperative for faculty members to encourage students to acquire creative thinking skills by providing a more challenging environment [25,26]. In addition, they need to employ their creative thinking in planning, implementation, and evaluation [27].…”
Section: Introductionmentioning
confidence: 99%
“…S obzirom da se u ovome radu bavimo korištenjem jezičnih igara u području jezika i jezičnoga izražavanja, detaljnije će biti pojašnjeni ciljevi tih dvaju područja nastave Hrvatskoga jezika. 2 Nastavno područje jezika (hrvatskoga jezika u užem smislu) obuhvaća sadržaje gramatike/slovnice, pravopisa i pravogovora standardnoga hrvatskoga jezika u nastavnome predmetu Hrvatski jezik u osnovnoj školi (Bežen, Budinski i Kolar Billege, 2012). Zadaće u jezičnome području su: osposobiti učenike za uspješno snalaženje u svakodnevnim priopćajnim situacijama, ovladavanje jezičnim sredstvima potrebnim za uspješnu komunikaciju, osvješćivanje potrebe za jezičnim znanjem, suzbijanje straha od jezika, osvješćivanje razlika između standardnoga jezika i zavičajnih idioma te postupno usvajanje hrvatskoga jezičnog standarda.…”
Section: Hrvatski Jezik U Osnovnoškolskoj Nastaviunclassified